Comparison of experimental competitive-exclusion cultures for controlling Salmonella colonization in broiler chicks - Revolledo,Liliana (2003)
The efficacy of three different types of experimental competitive exclusion (CE-A, CE-B and CE-C) cultures against Salmonella Kedougou (SK) NCTC 12173, resistant to nalidixic-acid resistant (NalR), in one-day-old broiler chicks, in four treatments with three replicates in each treatment, was evaluated. The mean logarithmic counts of Salmonella program of feces were 0.4 L in the group treated with CE-A, derived from the whole cecal contents of an adult bird with a mixture of aerobic and anaerobic bacterial cultures; 1.22 in the group treated with CE-B, containing aerobic bacterial culture; 1.00 in the group treated with CE-C, containing anaerobic bacterial culture; and 6.64 in the control group. The percentage of colonized birds varied from 10% to 26.66% in the treated groups and was 63.33% in the control group. A good protection (76.66% to 90%) was obtained in all treatments whereas lower protection was verified with experimental products containing only aerobic or anaerobic cultures. These results showed that a mixture of aerobic and anaerobic cultures can be effective for reducing SK colonization in broiler chicks.